(3eDSSI LhQL EjcgGQJ ddHMhK GdOhdjI Mhd GdcJH GdeOQSjI (B: (3JGQjN GdeDSSI hCgOGagG heLGdGJ YedgGs - (3cQGjfQ, LhfGKGfs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2007)
(3YQV GdHMK dJGQjN eDSSI (B"(3LhQL CcQJ(B" (3GdCdeGfjI ddHMhK GdOhdjI Mhd GdcJH GdeOQSjI eTjQkG Edi GdeSGQ GdJGQjNj dcJGH GdJGQjN ef eQMdI eG bHd GdMQH GdYGdejI GdChdi Edi CjGefG(B. (3hHYO GSJYQGV MjGI LhQL CcQJ (B(1912-1974) (3GdeDQN GdCdeGfj GdCUd, JTjQ GdOQGSI Edi OhQg aj ecGaMI GdJMQjV hGdJWQa Gdbhej hJeLjO GdMQhH aj GdcJH GdeOQSjI eeG OaYg aj SfI (B1951 (3Edi JCSjS GdeYgO GdOhdj dJMSjf GdcJH GdeOQSjI GdPj CUHM aj SfI (B1975 (3edcjI YGeI dCdeGfjG GdJj bQQJ Cf jMed GdeYgO GSe GdQLd GdPj CSSg(B. (3hHQCj (B"(3CcQJ(B" (3aEf ef GdCaVd, dMd eTcdGJ GdJYGed hGdJYUH, Cf JQqcR cJH GdJGQjN Ydi GdLhGfH GdGLJeGYjI hGdKbGajI hGdGbJUGOjI CcKQ ef GdLhGfH GdSjGSjI hCYeGd GdRYeGA(B. (3hjcQQ GdHMK Cf ZGjI eDSSI LhQL CcQJ gj GdYed Ydi JMSjf GdYdGbI Hjf GdCee hGdTYhH hGdLeGYGJ YHQ GSJHYGO GdJMQjV hGdJfejW GdSdHj ddfGS ef GdcJH GdJYdjejI, hJSdjW GdVhA Ydi GdJYGhf hGdSdGe hGdJYOOjI aj GdBQGA hGdehGba(B. (3hef GdfGMjI GdYedjI SGgeJ GdeDSSI aj EfJGL cJH GLJeGYjGJ ddHhSfI hGdgQSc hchShaG hGdCQGVj GdadSWjfjI GdeMJdI HYO Cf CTQaJ Ydi eTQhYGJ cKjQI dUjGZI eVGejf cJH GdJGQjN aj aQfSG hCdeGfjG hHhdfOG hHQjWGfjG(B. (3haj GdSfhGJ GdCNjQI TQYJ eDSSI (B"(3CcQJ(B" (3HELQGA OQGSGJ Mhd UhQI GdESdGe aj GdcJH GdeOQSjI GdChQhHjI hMhd UhQI GdZQH aj GdcJH GdeOQSjI GdYQHjI EVGaI Edi cJH JGQjN Yf GdUQGY GdYQHj(B-(3GdESQGFjdj(B. (3hbO hGLg GdeDdahf aj cd gPg GdMGdGJ eTcdI CSGSjI JJeKd aj cjajI GNJUGQ bVGjG eYbOI aj GdcJH GdeOQSjI Ohf JfejW eVehf gPg GdcJHs
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Livres Scolaires; Textbooks; (3GdcJGH GdeOQSjs; (3eDSSI LhQL EjcgGQJ ddHMhK GdOhdjIs